Fresh-cut pepper preservative film as well as preparation method and application thereof

By using composite films prepared by lignin nanoparticles, sodium alginate and tea polyphenols, the problem of perishable deterioration of freshly cut peppers is solved, and better preservation effect and environmental protection performance are achieved.

CN119591914AActive Publication Date: 2025-03-11HUNAN ACAD OF FORESTRY +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411779678.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The prior art is difficult to effectively preserve fresh and cut chili peppers, resulting in perishability, moisture loss, enzyme browning and nutritional loss, and traditional petroleum-based plastic wrap has environmental pollution problems.

Method used

Composite films are prepared by materials such as lignin nanoparticles, sodium alginate and tea polyphenols. Through uniformly distributed lignin nanoparticles and tea polyphenols, the antibacterial, antioxidant and ultraviolet shielding properties of the composite film are improved.

Benefits of technology

It significantly improves the freshness of freshly cut chili peppers, extends shelf life, reduces moisture loss and enzyme browning, has good thermal and anti-fog properties, and is environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005172485050000071
    Figure BDA0005172485050000071
  • Figure BDA0005172485050000081
    Figure BDA0005172485050000081
  • Figure BDA0005172485050000082
    Figure BDA0005172485050000082
Patent Text Reader

Abstract

The invention relates to the technical field of chili preservation, in particular to a fresh-cut chili preservative film as well as a preparation method and application thereof. The preparation method of the fresh-cut pepper preservative film comprises the following steps: S1, preparation of lignin nanoparticles LNP: dissolving lignin in a solution; then, water is dropwise added at the speed of 0.3 mL / min to 1.0 mL / min; and stirring, reacting at room temperature for 1-3 hours, standing and dialyzing to obtain the lignin nano-particles LNP, s2, preparation of a film forming solution: dissolving sodium alginate in water to obtain a sodium alginate solution; sequentially adding tea polyphenol and glycerol, and uniformly mixing to obtain a film forming solution; and S3, preparation of a composite film: adding lignin nanoparticles LNP into the film forming liquid, uniformly mixing, pouring, and drying to obtain the fresh-cut pepper preservative film. The fresh-cut pepper preservative film disclosed by the invention is relatively good in antibacterial performance and relatively low in water vapor transmission rate, and has excellent ultraviolet shielding performance and anti-fog performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pepper preservation, and more specifically, to a fresh-cut pepper preservative film and a preparation method and application thereof. Background Art

[0002] Peppers are popular because they are rich in vitamins, minerals and other nutrients. Fresh-cut products have become an indispensable fresh, nutritious and convenient fresh processed agricultural product in people's lives. They are invested in the catering industry in large quantities, and the market demand for such agricultural products is gradually increasing. Due to mechanical action, fresh-cut fruits and vegetables are prone to breeding bacteria on the cuts, which can easily cause problems such as spoilage, short storage time, water loss, enzyme browning, and nutrient loss. Maintaining the color, hardness, and freshness of fresh-cut fruits and vegetables is the key to maintaining quality. Fresh-cut peppers will damage the plant's tissue structure due to cutting and peeling, causing plant tissue injury, juice outflow, accelerated respiration, enzymatic and non-enzymatic browning, and increased physiological metabolic rate; in addition, large-area surface exposure and rich nutrition create an environment suitable for microbial growth, becoming a place for decay-causing bacteria to invade and reproduce, making fresh-cut peppers more prone to spoilage. Therefore, it is more difficult to preserve fresh-cut peppers. There are no relevant reports on the biological green and low-energy preservation method of fresh-cut peppers, nor are they used in the market.

[0003] Among the currently popular pepper preservation technologies, food packaging technology is widely used due to its versatility and easy handling. Its barrier and antibacterial properties determine the speed of food quality deterioration and shelf life. However, most of the current food packaging films are made of petroleum-based products. Due to their difficulty in degradation, their large-scale use has caused serious environmental pollution. Biomass polymers have broad application prospects in the food packaging industry due to their biocompatibility, biodegradability, low cost and environmental friendliness. Lignin is a natural polymer with the advantages of abundance, environmental protection, biocompatibility and biodegradability. Using it to prepare composite film materials can improve the strength and functionality of the materials. However, the poor dispersibility of lignin restricts its application in composite functional materials. At present, the application of lignin in food packaging is mostly combined with metal nanoparticles. However, the safety performance of metal nanoparticles is insufficient, which hinders its further application in food packaging.

[0004] The prior art discloses a slow-release antibacterial chitosan-based composite film, but the chitosan-based composite film has poor UV resistance and cannot meet the requirements for preserving fresh-cut food.

[0005] The prior art discloses a ternary composite material of lignin nanoparticles / polyvinyl alcohol / chitosan (LNP / PVA / CH). However, the antibacterial property of the ternary composite material is poor and cannot meet the requirements for preserving fresh-cut food. Summary of the invention

[0006] The purpose of the present invention is to provide a fresh-keeping film which has antibacterial properties and meets the requirements for preserving fresh-cut peppers, and a preparation method and application thereof.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing a fresh-cut pepper preservative film comprises the following steps:

[0009] S1. Preparation of lignin nanoparticles LNP: dissolving lignin in a solution; then adding water dropwise at a rate of 0.3-1.0 mL / min; stirring, reacting at room temperature for 1-3 hours, standing, and dialyzing to obtain the lignin nanoparticles LNP;

[0010] S2, preparation of film-forming solution: dissolving sodium alginate in water to obtain a sodium alginate solution; adding tea polyphenols and glycerol in sequence and mixing evenly to obtain a film-forming solution;

[0011] S3. Preparation of composite film: adding lignin nanoparticles LNP into the film-forming liquid, mixing evenly, pouring and drying to obtain a fresh-cut pepper cling film.

[0012] In a preferred embodiment, in S1, the stirring speed is 800-1200 r / min.

[0013] In a preferred embodiment, the lignin nanoparticles LNP are in granular form with a particle size of 90-160 nm.

[0014] Smaller particle sizes allow for more uniform dispersion, helping to improve the mechanical properties of composite materials. However, if the particle size is too small or unevenly distributed, it may lead to stress concentration, which reduces the strength of the material. At the same time, smaller particle size and more uniform distribution lead to higher transparency. Smaller and evenly distributed lignin nanoparticles can enhance the barrier properties of the composite film and prevent small molecules from passing through.

[0015] If the particle size is too large, it will be difficult to distribute evenly during the film-forming process, which may cause the film surface to become rough and uneven, affecting its appearance. Although lignin itself has certain thermal and chemical stability, if the prepared LNPs particle size is too large, it may change its surface properties by exposing more internal structures, thus affecting the performance of the composite film in these two aspects.

[0016] In a preferred embodiment, in S2, the mass ratio of sodium alginate, tea polyphenols and glycerol is (1-3):(1-3):(0.5-1.5).

[0017] In a preferred embodiment, in S2, the mass ratio of sodium alginate to tea polyphenols is 1-2:1-2.

[0018] In a preferred embodiment, in S2, the mass ratio of sodium alginate to tea polyphenols is 1:1.

[0019] Too little sodium alginate content will result in poor water vapor permeability of the composite film and poor film-forming properties of the composite film; while excessive sodium alginate will cause changes in the mechanical properties of the composite film, causing the film to become too rigid or fragile and easy to break.

[0020] If the content of tea polyphenols is too much, the cost of the composite film will increase too much; if the content is too little, its antibacterial performance will be weak.

[0021] In a preferred embodiment, in S2, the mass ratio of sodium alginate to water is 1-3:90-110.

[0022] In a preferred embodiment, in S3, the pouring is carried out on an acrylic board.

[0023] In a preferred embodiment, in S3, the drying temperature is 50-70°C and the drying time is 24-72h.

[0024] In a preferred embodiment, in said S3, the added amount of lignin nanoparticles LNP is 1%-5% of the total mass of sodium alginate and tea polyphenols.

[0025] If the LNPs content is too little, the mechanical properties and UV shielding properties of the composite film will be weak, while excessive LNPs will interfere with the hydrogen bonds between sodium alginate, weaken the bonding between the molecular bonds of sodium alginate, reduce the mechanical properties, and have poor dispersibility and stability.

[0026] In a preferred embodiment, in S3, the added amount of lignin nanoparticles LNP is 3%-5% of the total mass of sodium alginate and tea polyphenols.

[0027] In a preferred embodiment, in S3, the added amount of lignin nanoparticles LNP is 5% of the total mass of sodium alginate and tea polyphenols.

[0028] Based on the same inventive concept, the present invention also claims protection for the fresh-cut pepper preservative film prepared by the preparation method.

[0029] In a preferred embodiment, the thickness of the fresh-cut pepper preservative film is 0.090-0.095 mm.

[0030] In a preferred embodiment, the maximum thermal decomposition temperature of the fresh-cut pepper cling film is 183-194°C.

[0031] In a preferred embodiment, the moisture content of the fresh-cut pepper preservative film is 31%-37%.

[0032] In a preferred embodiment, the water vapor permeability of the fresh-cut pepper cling film is 0.02-0.05%.

[0033] Based on the same inventive concept, the present invention also claims to protect the application of the fresh-cut pepper preservative film in preserving fresh-cut vegetables.

[0034] In a preferred embodiment, the fresh-cut vegetables are fresh-cut peppers.

[0035] Based on the same inventive concept, the present invention also claims to protect the application of fresh-cut pepper cling film in antibacterial, antioxidant and anti-ultraviolet applications.

[0036] Compared with the prior art, the fresh-cut pepper cling film prepared by the present invention has the following advantages and significant improvements: (1) LNPs and TP produce a synergistic effect of antibacterial and antimicrobial after being compounded, which destroys the cell membrane structure of the bacteria, interferes with the normal function of the bacterial DNA, hinders the synthesis and expression of bacterial proteins, accelerates the exudation of contents and causes cell death. (2) LNPs and TP can be evenly distributed in SA, the integrity of the composite film is better, and the addition of LNPs and TP not only improves the mechanical properties of the composite film, but also improves the structural properties of SA. The water vapor permeability of the prepared composite film is low. At the same time, due to the color development of lignin and TP itself, the prepared composite film appears brown, so that the prepared composite film has excellent ultraviolet shielding properties in both UVA and UVB bands. (3) The composite film can significantly improve the freshness of fresh-cut peppers and extend their shelf life. (4) The composite film has good hot anti-fog properties and cold anti-fog properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 are the morphology and size results of LNPs; where a is the microscopic morphology of 1-LNPs lignin nanoparticles; b is the microscopic morphology of 3-LNPs lignin nanoparticles; c is the microscopic morphology of 5-LNPs lignin nanoparticles; A is the particle size distribution of 1-LNPs; B is the particle size distribution of 3-LNPs; C is the particle size distribution of 5-LNPs;

[0038] Figure 2 The appearance photos of SA / TP / LNPs composite films; (a) is the control film; (b)-(d) the addition amounts of lignin nanoparticles are 1%, 3%, and 5%, respectively;

[0039] Figure 3SEM images of SA / TP / LNPs composite films; (a) control film; (b) lignin nanoparticles added at 5%;

[0040] Figure 4 The barrier properties of SA / TP / LNPs composite film to visible light and ultraviolet light;

[0041] Figure 5 TG-DTG curves of the film, A is the TG curve, B is the DTG curve;

[0042] Figure 6 Anti-fogging performance of SA / TP / LNPs composite film;

[0043] Figure 7 The antibacterial properties of SA / TP / LNPs composite membrane against Escherichia coli and Staphylococcus aureus;

[0044] Figure 8 The free radical scavenging ability and total antioxidant capacity of SA / TP / LNPs composite film;

[0045] Fig. 9 The effects of different treatment groups on the appearance of fresh-cut peppers;

[0046] Fig.10 The weight loss rate of fresh-cut pepper during storage;

[0047] Fig.11 The effect of different treatments on the decay index of fresh-cut peppers after 10 days of storage;

[0048] Fig.12 The change of soluble solids content in fresh-cut pepper during storage;

[0049] Fig.13 The changes of Vc content in fresh-cut pepper during storage;

[0050] Fig.14 The changes of respiration intensity during storage of fresh-cut peppers;

[0051] Fig.15 To study the changes of chlorophyll in fresh-cut pepper during storage;

[0052] Fig.16 Changes of malondialdehyde during storage of fresh-cut peppers. DETAILED DESCRIPTION

[0053] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0054] Data statistics and analysis of the present invention: All experiments were repeated 3 times, and the results were expressed as mean ± standard deviation. SPSS 20.0 software was used for one-way analysis of variance, and Origin 8.5 was used for plotting.

[0055] The strains, materials and reagents used in the present invention are as follows:

[0056] Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) are laboratory preserved strains; alkaline lignin; tetrahydrofuran (AR), sodium alginate (chemically pure), glycerol (AR), methanol (AR) and other analytically pure products were purchased from Sinopharm Chemical Reagent Co., Ltd.; tea polyphenols (99%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; chromatographically pure 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) was purchased from Hangzhou Huipu Chemical Co., Ltd.; 2,2'-azobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), anhydrous calcium chloride, and deionized water were used for the experiment; Zhangshugang pepper. Other reagents not specified are all common commercial products on the market.

[0057] The instruments and equipment used in the present invention are as follows:

[0058] Nano ZS90 Malvern laser particle size analyzer, Malvern, UK; Evolution 201 UV-visible spectrophotometer, Thermo Fisher Scientific Inc.; Discovery TGA550 thermogravimetric analyzer, Thermal Analysis Instruments, Inc., USA; Nicolet iS50 Fourier transform infrared spectrometer, Nicolet, USA; ZEISS Sigma300 scanning electron microscope, Carl Zeiss AG, Germany; MTS CMT6103 electronic universal testing machine, Shenzhen Century Tianyuan Instrument Co., Ltd.; blast drying oven, Suzhou Ruizhifeng Oven Manufacturing Co., Ltd.; magnetic heating stirrer Guohua Electric Co., Ltd.; JA2003 electronic balance, Shanghai Hengping Scientific Instrument Co., Ltd.; GZ-280-S biochemical incubator, Shaoguan Guangzhi Technology Equipment Co., Ltd.; BBS-SDC clean bench, Jinan Xinbeisi Biological Co., Ltd.; digital micrometer, Dongguan Sanliang Hardware Instrument Co., Ltd.; PAL-BX / ACID1 saccharimeter, Japan ATAGO Co., Ltd.

[0059] Example 1

[0060] 1. Preparation method of lignin nanoparticles

[0061] Weigh an appropriate amount of lignin and use water as an anti-solvent to prepare LNPs. Add an appropriate amount of lignin components dissolved in H2O-tetrahydrofuran co-solvent (H2O-tetrahydrofuran v / v, 3 / 7) into a round bottom flask and stir magnetically to fully dissolve the lignin to obtain LNPs solutions with mass concentrations of 1%, 3% and 5%. Then use a dropping funnel to drip 40mL of deionized water into the lignin solution at a rate of about 0.5mL / min, and stir continuously at room temperature for 2h at a stirring rate of 1000r / min. The formed LNPs are recorded as 1-LNPs, 3-LNPs, and 5-LNPs. Place the suspension in a dialysis bag, and then immerse the dialysis bag in excess deionized water to remove tetrahydrofuran (deionized water needs to be replaced regularly).

[0062] The morphology and particle size of 1-LNPs, 3-LNPs and 5-LNPs were characterized by SEM and nanoparticle size analyzer. The results are as follows: Figure 1 As shown. SEM images show that the prepared lignin products are nano-scale particles, showing spherical and granular structural characteristics. Among them, the average particle size of 1-LNPs is the smallest at 98.33±4.58nm, and the average particle size of 5-LNPs is the largest at 150±2.31nm, with good dispersibility. However, the concentration of LNPs solution is too high. For example, the particle size of 10-LNPs with a mass concentration of 10% is too large at 573±6.98nm, and the dispersibility (dispersion coefficient PDI is 2.231) and stability are poor.

[0063] 2 Preparation of film-forming solution and composite film

[0064] Preparation of SA / TP membrane-forming solution: First, weigh 2g of sodium alginate SA and dissolve it in 100mL of deionized water, stir at 60℃ for 2h until the solution is transparent and free of bubbles, and prepare a 2wt% SA solution. Then weigh 2g of tea polyphenols TP and dissolve it in the SA solution, stir evenly, and then add 1% glycerol to it, mix evenly to obtain a SA / TP mixed membrane solution for use.

[0065] Preparation of SA / TP / LNPs film-forming solution: Mix the SA / TP mixed film solution with a certain amount of LNPs with a mass concentration of 1% and mix them evenly. Finally, pour the film-forming solution onto an acrylic plate, flatten it, and dry it at 60°C for 48 hours to form a film. According to the amount of LNPs added (relative to the mass fraction of SA / TP), the mass fractions were 1%, 3%, and 5%, respectively, and the composite films were named: SA / TP / LNPs-1, SA / TP / LNPs-3, and SA / TP / LNPs-5.

[0066] Composite membrane testing and characterization

[0067] 1 SEM characterization of composite membranes

[0068] The composite membrane was cut into strips of appropriate size and treated with gold spraying. The surface morphology of the membrane was detected using a scanning electron microscope (ZEISS Sigma300).

[0069] Since LNPs and TP are brown, the composite membrane prepared from LNPs and TP materials is also brown. Figure 2 The SEM characterization results are shown in Figure 3 As shown. Figure 2 It can be seen that with the increase of LNPs content, the appearance of the composite film changes from light brown to dark brown, and its transparency decreases. Figure 3 It can be seen that the SA / TP / LNPs composite film exhibits a relatively uniform and continuous surface without large-scale agglomeration, indicating that LNPs and TP have good dispersion in SA and no phase separation occurs. There are no pores and cracks between LNPs and SA, indicating that good interfacial connection can serve as a bridge for load transfer, reduce stress concentration under strain, and thus improve the toughness and ductility of the antibacterial composite film.

[0070] 2. Light transmittance test of composite film

[0071] The composite film was cut into a rectangle of 10 mm×40 mm, and its transmission spectrum was measured in the wavelength range of 200 to 800 nm using a UV-visible spectrophotometer, with a blank cuvette used as a control.

[0072] The results are as follows Figure 4 As shown in the figure, the barrier properties of SA film, SA / TP film and PE film to visible light and ultraviolet light are poor, and the visible light transmittance is above 70%. Compared with SA film and SA / TP film, SA / TP / LNPs composite film almost completely blocks the spectrum of UVB (320-275nm) and UVC (275-200nm) and most of UVA (400-320nm). Even if the amount of LNPs added is small, the UV shielding performance of the composite film can be significantly enhanced.

[0073] 3 Thermogravimetric analysis

[0074] An appropriate amount of composite film sample was weighed, and the temperature was raised from room temperature to 600°C at a heating rate of 10°C / min in a nitrogen atmosphere to measure the thermal stability of the composite film.

[0075] The thermal stability of several films was studied. The TG-DTG curves of the films are shown in Figure 2. Figure 5As shown, A is the TG curve and B is the DTG curve. The maximum thermal decomposition temperature of the SA film is 179.5°C. With the addition of LNPs and TP, the maximum thermal decomposition temperature of the composite film is increased. The maximum thermal decomposition temperatures of SA / TP / LNPs-1, SA / TP / LNPs-3 and SA / TP / LNPs-5 are 183.2°C, 190.3°C and 193.4°C, respectively. The results show that the composite film has good thermal stability.

[0076] 4 Antibacterial effect of composite membrane liquid

[0077] Pour the nutrient agar medium into a sterile culture dish and, after solidification, add 0.1 mL of 10 6 CFU / mL bacterial suspension was evenly spread on the surface of the culture medium with a coating rod. Four holes were punched on the agar with a sterilized puncher, three of which were filled with composite membrane solution, and one was filled with LNPs solution as a blank. The cells were cultured at 37℃ for 12-24h, the size of the inhibition zone was observed, and the colony diameter was determined by the cross method.

[0078] The test results show that the composite membrane liquid has a good inhibitory effect on Staphylococcus aureus and Escherichia coli, as shown in Table 1. The antibacterial effect on Staphylococcus aureus is the most obvious, the antibacterial activity on Escherichia coli is relatively weak, and the antibacterial effect is positively correlated with the mass concentration of tea polyphenols.

[0079] Table 1 Determination results of the inhibition zone of the composite membrane liquid against two foodborne pathogens

[0080]

[0081]

[0082] Note: Different lowercase letters after the values ​​in the same column indicate significant differences (P < 0.05)

[0083] When the mass ratio of SA to TP is 3:1, the antibacterial performance of the prepared composite film is reduced, and the prepared composite film is easy to break due to the increase in the amount of sodium alginate. When the mass ratio of SA to TP is 4:1, the composite film solution has poor fluidity and high viscosity, and the composite film solution is difficult to stir and uneven, making it difficult to form a uniform film during the casting process.

[0084] Determination of physical and chemical testing indicators of composite membranes

[0085] 1Thickness

[0086] The film thickness was measured using a digital micrometer at 10 random locations on the film sample.

[0087] 2. Determination of moisture content and water solubility

[0088] The film was divided into 20 mm × 20 mm squares, and then the initial mass was measured. The film was dried at 105 ° C until a constant mass was obtained, and the moisture content was calculated according to formula (1). The film was completely dried and then soaked in 50 mL of distilled water at room temperature for 24 h. The swollen film was then taken out of the solution and dried at 105 ° C until a constant mass was obtained, and the water solubility (%) was calculated using formula (2):

[0089]

[0090] Where: m0 is the mass of the initial film / g; m1 is the dry mass of the film after drying / g; m2 is the dry mass of the film after swelling / g.

[0091] 3 Mechanical properties

[0092] The film was cut into rectangles of 100 mm × 10 mm, and its tensile strength (TS, MPa) and elongation at break (EAB, %) were measured using an automatic tensile testing machine. The initial clamping distance was 50 mm, and the clamping speed was 1 mm / s.

[0093] 4 Water vapor transmission rate

[0094] A film (60mm×60mm) containing anhydrous calcium chloride (particle size less than 2mm) is fixed on the mouth of the test cup, and the distance between calcium chloride and the mouth of the cup is less than 6mm. The weighing test cup is placed in a saturated sodium chloride solution (25℃, 75% relative humidity) dryer to maintain a certain vapor pressure difference inside and outside the film. Remove the test cup and weigh it regularly until the mass change is less than 0.001g. Each experiment is repeated 3 times. The WVP calculation formula is as follows:

[0095]

[0096] Where: m is the mass change of water during the test, g; L is the thickness of the film sample, mm; A is the area of ​​the weighing bottle mouth, m 2 ; t is the test time, s; p2 is the water vapor partial pressure of water at 20°C, 2.337 kPa; p1 is the water vapor partial pressure in the silica gel desiccant, 0.0280 kPa.

[0097] Table 2 shows that the thickness of the prepared SA / TP / LNPs composite films with different ratios has no significant difference (P>0.05), ranging from 0.090 to 0.093 mm. Compared with the SA film, the thickness of the composite film increases with the addition of TP and LNPs. The thickness of the PE film is 0.089 mm, and the thickness of the SA / TP / LNPs composite films with different ratios has no significant difference with that of the PE film (P>0.05).

[0098] Table 2 Physical properties of seven membrane materials

[0099]

[0100] Note: If the lowercase letters after the data in the same column are completely different, it means that the difference between the groups is significant (P<0.05), and if there is any identical lowercase letter, it means that the difference is not significant (P>0.05).

[0101] The moisture content of SA film is significantly higher than that of other composite membranes. With the addition of TP, the moisture content of SA / TP composite membrane drops to 47.20%. After the introduction of LNPs, the moisture content of SA / TP / LNPs composite membrane is greatly reduced. The moisture content of SA / TP / LNPs-5 is the lowest at 31.06%, followed by SA / TP / LNPs-3 (34.72%) and SA / TP / LNPs-1 (36.81%). Overall, the moisture content of the composite membrane gradually decreases with the increase of LNPs content.

[0102] Among all the prepared membranes, SA film had the highest water solubility at room temperature (79.62%), which was due to the hydrophilicity of SA and glycerol. The water solubility of the composite membranes decreased significantly after the addition of LNPs and TP (P<0.05). SA / TP / LNPs-5 had the lowest solubility of 44.54%, followed by SA / TP / LNPs-3 (54.29%) and SA / TP / LNPs-1 (62.42%). The higher water resistance of the composite membranes indicated the cross-linking and miscibility of the phenolic compounds of lignin with the hydrophilic part of sodium alginate.

[0103] Water vapor permeability is an important indicator of the transfer of ambient atmospheric water vapor to the other side of the film, which will affect the shelf life of the packaged product. The WVP data of the composite film are shown in Table 2. The water vapor permeability of the SA film is as high as 0.101%. The hydrophilicity of SA makes the barrier property of the composite film worse. The WVP of the SA / TP / LNPs composite film is significantly lower than that of the SA film and the PE film (P<0.05), among which the WVP of SA / TP / LNPs-5 is as low as 0.028%. Under the same conditions, the water vapor permeability of the composite film prepared by the prior art CN 113292753 B is 2.608 when w(LNP):w(ASPNG) is 3:5. Repeat the prior art CN 113652047B Example 10 to prepare a composite film with a ternary composite material of lignin nanoparticles / polyvinyl alcohol / chitosan (3LNP / PVA / CH), and the water vapor permeability is 3.154. The water vapor permeability of both is much greater than that of the SA / TP / LNPs composite film prepared by the present invention.

[0104] Food packaging materials should have good mechanical properties to meet the requirements of food packaging. Mechanical properties are an indispensable parameter for determining the structural integrity of active packaging films. As shown in Table 2, SA film has a higher elongation at break (EB) and a lower tensile strength (TS). Compared with the single SA film, the tensile strength of the composite film SA / TP is improved and the elongation at break is reduced. The TS of the composite films SA / TP / LNPs-3 and SA / TP / LNPs-5 are much greater than those of sodium alginate and other composite films, which are 5.33MPa and 6.44MPa respectively.

[0105] 5. Determination of anti-fog performance of composite film

[0106] Thermal anti-fog test: Cover the composite film on a beaker filled with 50°C water (about 60 mL) and place it in a 50°C water bath. Observe the fogging on the film surface at 0 min, 60 min, and 120 min to evaluate its thermal anti-fog performance.

[0107] Cold anti-fog test: Cover the beaker with the composite film, place it at -20℃ for 2h, then place it at room temperature (25℃) for 30s, observe the fogging on the film surface and evaluate its cold anti-fog performance.

[0108] Due to changes in ambient temperature, the surface of the packaging material will be atomized, and water molecules will condense on the surface of the material to form water droplets. The formation of mist droplets can cause the growth of microorganisms, so the packaging material is required to have good anti-fog properties. Figure 6 As shown in the figure, at 60min and 120min in the water bath, the droplets gathered on the surface of the PE film and the background text became blurred. However, no water droplets formed on the surface of the SA / TP / LNPs composite film, indicating that it has good hydrophobicity, water absorption and anti-fogging properties. At the same water bath time, the transparency of the SA / TP / LNPs composite film is higher than that of the SA film. For low-temperature anti-fogging, the surface of the PE film quickly fogged when it was transferred from -20℃ to room temperature. No fog droplets were formed on the surface of the composite film, which has better anti-cold fogging performance than the SA film alone.

[0109] Under the same conditions, the anti-fog properties of the composite film prepared by the prior art CN 113292753 B with w(LNP):w(ASPNG) being 3:5 and the composite film prepared by the ternary composite material of lignin nanoparticles / polyvinyl alcohol / chitosan (3LNP / PVA / CH) prepared by Example 10 of the prior art CN 113652047 B were both worse than those of the SA / TP film.

[0110] 6 Determination of antibacterial properties of composite films

[0111] An appropriate amount of composite membrane was immersed in liquid culture medium (20 mL) and inoculated with 500 μL of E. coli or S. aureus suspension (10 8CFU / mL), cultured in a constant temperature shaker (150r / min, 37℃) for 12h, sampled, diluted to an appropriate concentration, evenly applied to the culture medium, and counted. The inhibition rate was calculated according to formula (4).

[0112]

[0113] Where: N 对照 N is the number of colonies on the control plate; 样品 is the number of colonies on the plate of the sample group with composite membrane added.

[0114] The results are as follows Figure 7 As shown in the figure, compared with SA film and PE film, SA / TP / LNPs composite film has better antibacterial effect, among which composite film SA / TP / LNPs-5 has the best antibacterial efficiency, with an antibacterial rate of 91.28% against S. aureus and 89.20% against E. coli, which are better than composite films SA / TP / LNPs-1 and SA / TP / LNPs-3. The antibacterial efficiency of composite film SA / TP / LNPs-5 is also better than that of SA / TP film.

[0115] 7 Determination of antioxidant properties of composite films

[0116] In order to improve the reliability of the experiment, the ABTS and DPPH free radical scavenging rates of the composite membrane were determined simultaneously. Weigh 0.1g of the composite membrane sample and add it to a conical flask filled with distilled water. Stir magnetically (150r / min) at 25℃ for 24h until it is completely dissolved for use. Mix 1mL of DPPH methanol solution with a concentration of 1mmol / L with 3mL of the composite membrane solution, store it in the dark at room temperature for 30min, and test the antioxidant activity. Then use an ultraviolet spectrophotometer to measure the absorbance of the mixture at 517nm. Use methanol as a blank control to measure the absorbance. The DPPH free radical scavenging rate is calculated according to formula (5).

[0117]

[0118] Where: A sample is the absorbance of the sample, A control is the absorbance of the control group.

[0119] The ABTS cation radical scavenging rate was determined according to the method of Yuan et al. with slight modifications. 1.0 mL of the eluent was mixed with 2.0 mL of the ABTS reaction solution, and 50% ethanol was used as a blank control. The mixture was reacted at room temperature in the dark for 1 h. The absorbance of the mixed solution at a wavelength of 734 nm was measured using a UV-visible spectrophotometer. The ABTS cation radical scavenging rate was calculated according to formula (6).

[0120]

[0121] Where: A sample is the absorbance of the sample, A control is the absorbance of the control group.

[0122] The results are as follows Figure 8 It can be seen that the free radical scavenging ability and total antioxidant capacity of the SA / TP / LNPs composite film are better than those of the SA film, SA / TP film and PE film. With the increase of the LNPs content in the composite film, the free radical scavenging ability and total antioxidant capacity of the composite film gradually increase, and the composite film SA / TP / LNPs-5 has the best effect.

[0123] Under the same conditions, the free radical scavenging ability and total antioxidant capacity of the composite film prepared by the prior art CN 113292753 B with w(LNP):w(ASPNG) being 3:5 and the composite film prepared by the lignin nanoparticle / polyvinyl alcohol / chitosan (3LNP / PVA / CH) ternary composite material prepared by Example 10 of the prior art CN 113652047 B were tested, and the scavenging rate was only half of that of the SA / TP film.

[0124] Example 2

[0125] Application of SA / TP / LNPs composite film in the preservation of fresh-cut peppers

[0126] 1. Pepper sample processing

[0127] Treatment of fresh-cut peppers: Cut the rinsed and dried peppers into uniform small pieces and place them in food-grade polypropylene fresh-keeping containers. All peppers were randomly divided into 5 groups, namely blank control (CK), PE film, SA film, SA / TP composite film and SA / TP / LNPs-5 composite film. Among them, all peppers were stored at room temperature (25±2℃) and humidity (85%-90%) for 10 days, and samples were randomly selected from each group every 2 days for the determination of various indicators.

[0128] The appearance of fresh-cut peppers was observed with the naked eye. Fig. 9As shown. During the initial storage period, there was no significant difference in the appearance of the samples in each group. From the 8th day, both the CK group and the PE group showed obvious color changes, and the CK group showed partial tissue decay. In the absence of any treatment, the fragile cell structure on the cross section of the fresh-cut bell pepper led to the loss of nutrients. At the same time, the attachment and proliferation of microorganisms further destroyed the intrinsic defense mechanism of the pepper, resulting in a rapid decline in the quality of the pepper in the later stage of storage. By the 10th day, the quality of the CK group and the SA group deteriorated further, showing more severe decay, while the color change of the fresh-cut pepper in the PE group was more obvious than that in the early stage of storage. In contrast, the SA / TP / LNPs-5 composite film group and the SA / TP group did not show obvious color changes or signs of decay. In summary, the SA / TP / LNPs-5 composite film effectively delayed the deterioration of the quality of fresh-cut green peppers.

[0129] Under the same conditions, the preservation effect of the composite film prepared by the prior art CN 113292753 B with w(LNP):w(ASPNG) of 3:5 and the composite film prepared by the lignin nanoparticles / polyvinyl alcohol / chitosan (3LNP / PVA / CH) ternary composite material prepared by Example 10 of the prior art CN 113652047 B on fresh-cut peppers was tested. Both showed obvious color changes and signs of decay.

[0130] 2 Determination of weight loss rate

[0131] The weight loss rate is calculated according to the following formula

[0132]

[0133] Where: m0 is the initial mass of the pepper before treatment, g; m1 is the mass of the pepper after soaking and leaving for several days, g.

[0134] During storage, water loss caused by cutting of fresh-cut peppers is considered to be the main cause of weight loss of fresh-cut peppers. Fig.10 As shown in the figure, the weight loss rate of all peppers showed an upward trend with the extension of storage time. On the 6th day of storage, the weight loss rate of peppers in the CK group rose sharply to 33.83%, and the weight loss rate of the PE group was 22.62%, which was significantly different from the weight loss rate of peppers in the SA / TP / LNPs-5 composite membrane group (13.28%) (P < 0.05). On the 10th day of storage, the weight loss rate of the SA / TP / LNPs-5 composite membrane group was only 16.62%, which was much lower than that of the CK group, SA / TP group and PE group. This may be because the film on the surface of the green pepper formed an effective barrier, reducing water loss and respiratory activity, thereby maintaining the quality of fresh-cut peppers. At the same time, TP effectively inhibited the adhesion and growth of microorganisms, thereby slowing down the consumption of nutrients.

[0135] 3. Determination of decay index

[0136]

[0137] Decay rating:

[0138] Level 0: No decay;

[0139] Level 1: The rotten area accounts for 0% to 10% of the total fruit area;

[0140] Level 2: The rotten area accounts for 10% to 30% of the total fruit area;

[0141] Level 3: The rotten area accounts for 30% to 50% of the total fruit area;

[0142] Level 4: The rotten area accounts for 50%-100% of the total fruit area.

[0143] Fig.11 The effect of each treatment on the rot index of pepper fruit on the 10th day of storage. The rot index of the CK group reached 67.67%, the SA / TP / LNPs-5 composite film group had the lowest rot index of 20.67%, followed by the SA / TP composite film group with a rot index of 26.33%, and the PE group with a rot index of 36.32%. The SA / TP / LNPs-5 composite film group was 69.45% lower than the CK group and 43.09% lower than the PE group, indicating that the SA / TP / LNPs-5 composite film can inhibit the rate of pepper rot and deterioration.

[0144] 4. Determination of soluble solids

[0145] The soluble solids content of the fruit was measured using a PAL-BX / ACID1 saccharimeter, and the soluble solids were expressed in %.

[0146] Peppers from different treatment groups were squeezed into juice, which was then transferred into 10 mL centrifuge tubes and centrifuged at 4°C and 7000×g for 5 min. 20 μL of supernatant was accurately aspirated for measurement.

[0147] like Fig.12As shown in the data, the soluble solids content of fresh-cut peppers in each group continued to decrease during storage. After being cut, the peppers would have a certain degree of mechanical damage, which would increase their respiration and continuously consume soluble solids, resulting in a decrease in their content. Among them, the soluble solids content of fresh-cut peppers in the PE group decreased rapidly from 6.02% at the beginning of storage to 4.46%, which was significantly lower than that of the composite membrane treatment group during the entire storage process. The soluble solids content of fresh-cut peppers treated by the SA / TP / LNPs-5 composite membrane group remained at a high level, and its content was 4.88% on the 10th day of storage, which was only 18.94% lower than that before storage, and significantly lower than 36.88% in the CK group and 25.91% in the PE group. The soluble solids content of peppers in the SA / TP composite membrane group was lower than that of fresh-cut peppers treated by the SA / TP / LNPs-5 composite membrane group.

[0148] 5. Determination of Vitamin C Content

[0149] The content of vitamin C was determined by 2,6-dichloroindoxyl titration method.

[0150] Effects of different packaging methods on the content of vitamin C in fresh-cut peppers during storage Fig.13 As shown in the figure, it can be seen that during the storage process, the Vc content of peppers in the CK group decreased from 63 mg / 100 g at the beginning of storage to 30 mg / 100 g. PE and SA / TP / LNPs-5, SA / TP composite films can all delay the decline of Vc in fresh-cut peppers, but their effects are not as good as SA / TP / LNPs-5. On the 10th day of storage, the Vc content of fresh-cut peppers in the PE group was 41.33 mg / 100 g, while the Vc content of fresh-cut peppers in the SA / TP / LNPs-5 composite film group was 49.33 mg / 100 g. Compared with the CK group and the PE group, the Vc content increased by 39.19% and 16.22%, which was a large difference (p < 0.05), indicating that the homemade composite film containing TP and LNPs can prevent the oxidation of Vc and has good antioxidant capacity.

[0151] 6. Determination of respiratory intensity

[0152] The respiration intensity of peppers was determined by the static method. During the determination, the sample was placed in a dryer, and a quantitative alkali solution was placed at the bottom of the dryer. The CO2 released by the fruits and vegetables during respiration naturally sank and was absorbed by the alkali solution. After standing for 30 minutes, the alkali solution was taken out and titrated with oxalic acid to calculate the amount of CO2 released by the sample during respiration.

[0153]

[0154] Where: C-H2C2O4 solution molar concentration, moL / L;

[0155] V1—the amount of H2C2O4 used in blank titration, mL;

[0156] V2—the amount of H2C2O4 used in the titration, mL;

[0157] m—weight of fruits and vegetables, kg;

[0158] T—measurement time, h;

[0159] 22—Mass conversion number of NaOH and CO2 in the determination.

[0160] like Fig.14 As shown in the results, the respiration intensity of the five groups of samples showed a gradual increase during the entire storage period. On the 0th day of storage, the respiration rates of the CK group and the treatment group were basically the same. However, on the 4th day of storage, the respiration intensity of the CK group increased sharply to 23 mg / (kg·h), and the respiration intensity of the SA / TP / LNPs-5 group increased slightly to 17.16 mg / (kg·h). On the 10th day of storage, compared with the initial storage period, the respiration rate of the CK group increased significantly by 102.44%, and the respiration rate of the SA / TP / LNPs-5 group increased by 52.66%. The results show that the SA / TP / LNPs-5 composite film has a significant effect on regulating the respiration intensity of fresh-cut peppers, resulting in reduced oxidative metabolism.

[0161] 7 Determination of chlorophyll content

[0162] Take 0.2g of fresh sample in a mortar, add a small amount of quartz sand, 0.2g of calcium carbonate and 5mL of 95% ethanol, grind into a homogenate, add 95% ethanol and continue grinding until the tissue turns white, and let it stand for 5 minutes. Pour the extract into a funnel, filter it into a brown volumetric flask with 95% ethanol, rinse repeatedly until there is no green residue, and finally adjust the volume to 25mL. Use 95% ethanol as a blank and measure the absorbance at wavelengths of 665nm and 649nm.

[0163] The calculation formula is as follows:

[0164]

[0165] Where:

[0166] C a ,—Chlorophyll a concentration at a wavelength of 665nm;

[0167] C b - Chlorophyll b concentration at a wavelength of 649 nm;

[0168] V—total volume of sample extract, mL;

[0169] W—sample weight, g.

[0170] Chlorophyll is the main pigment that affects the color of peppers. The changes in pigments during storage are related to various factors such as the physiological state of peppers. Fig.15 As shown in the figure, on the 10th day of storage, the chlorophyll content of the SA / TP / LNPs-5 composite film group decreased from 0.26 mg / g to 0.17 mg / g, while the chlorophyll content of the CK group and the PE group decreased from 0.26 mg / g at the beginning of storage to 0.08 mg / g and 0.12 mg / g, respectively. This is consistent with the color change of fresh-cut peppers observed in the figure. The SA / TP / LNPs-5 treatment group had the smallest decrease in chlorophyll content, effectively maintaining the appearance and color of fresh-cut green pepper slices.

[0171] 8 Determination of malondialdehyde content

[0172] The determination was performed according to the malondialdehyde kit operation.

[0173] Effects of different packaging methods on the MDA content of fresh-cut peppers during preservation Fig.16 As shown. The results showed that the MDA content of the five groups of samples showed an upward trend during storage. On the 6th day of storage, the malondialdehyde content in the CK group increased sharply (1.26nmoL / g), which was significantly different from the MDA content in the PE group (0.816nmoL / g) and the SA / TP / LNPs composite membrane group (0.59nmoL / g) (p < 0.05). This indicates that free radicals and reactive oxygen accumulate on the cross section of fresh-cut bell peppers, leading to continued aggravation of lipid oxidation in the cell membrane. On the 10th day of storage, the MDA content in the CK group and the PE group was 1.74nmoL / g and 1.43nmoL / g, and the MDA content in the SA / TP / LNPs-5 composite membrane group was 0.95nmoL / g. The MDA content of SA / TP / LNPs-5 was lower than that in the CK group, PE group and SA / TP group. It shows that the composite film packaging containing LNPs and TP can effectively inhibit the accumulation of MDA in green pepper fruits during storage and reduce the membrane peroxidation damage of green pepper fruits.

[0174] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing a fresh-cut pepper preservative film, characterized in that: The following steps are involved: S1. Preparation of lignin nanoparticles LNP: dissolving lignin in a solution; then adding water dropwise at a rate of 0.3-1.0 mL / min; stirring, reacting at room temperature for 1-3 hours, standing, and dialyzing to obtain the lignin nanoparticles LNP; S2, preparation of film-forming solution: dissolving sodium alginate in water to obtain a sodium alginate solution; adding tea polyphenols and glycerol in sequence and mixing evenly to obtain a film-forming solution; S3. Preparation of composite film: adding lignin nanoparticles LNP into the film-forming liquid, mixing evenly, pouring and drying to obtain a fresh-cut pepper cling film.

2. The preparation method according to claim 1, characterized in that: The lignin nanoparticles LNP are in granular form with a particle size of 90-160 nm.

3. The preparation method according to claim 1, characterized in that: In S2, the mass ratio of sodium alginate, tea polyphenols and glycerol is (1-3):(1-3):(0.5-1.5).

4. The preparation method according to claim 3, characterized in that: In the S2, the mass ratio of sodium alginate to tea polyphenols is 1-2:1-2.

5. The preparation method according to claim 1, characterized in that: In the S2, the mass ratio of sodium alginate to water is 1-3:90-110.

6. The preparation method according to claim 1, characterized in that: In the above S3, the added amount of lignin nanoparticles LNP is 1%-5% of the total mass of sodium alginate and tea polyphenols.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In the above S3, the added amount of lignin nanoparticles LNP is 3%-5% of the total mass of sodium alginate and tea polyphenols.

8. A fresh-cut pepper preservative film prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the fresh-cut pepper preservative film according to claim 8 in preserving fresh-cut vegetables.

10. Use of the fresh-cut pepper cling film according to claim 8 in antibacterial, anti-oxidant and anti-ultraviolet radiation aspects.

Citation Information

Patent Citations

  • A method for preparing a sustained-release antibacterial chitosan-based composite membrane and its application

    CN113292753B

  • Lignin nanoparticle / polyvinyl alcohol / chitosan ternary composite materials, their preparation methods and applications

    CN113652047B

  • A shrimp bio-preservation film and its preparation method

    CN102268146A

  • Tea polyphenol-containing carrageenan-based edible anti-oxidation membrane and preparation method thereof

    CN109734968A

  • Sodium alginate preservative film, preparation method and application thereof

    CN110511443A